The Effect of Storage Conditions on the Absorption Profile of 2% Lydocaine Hydrochloridum Injection by UV-Vis Spectrophotometry - Dian Marlina; Sephia Febriyanti; Arsyeni Destra Anarchy Arsyandi; Nur Anggreini Dwi Sasangka (Universitas PGRI Semarang, 2023)
Lidocaine HCl injection is a sterile product that is easily contaminated when opened. The temperature and humidity in the injection storage conditions also affect the quality of the drug when viewed from the UV-Vis spectrophotometric absorption value. The aimed of this study is to find out how the effect of storage conditions on the absorption profile of 2% lydocaine HCl injection by UV-Vis spectrophotometry. The study used 27 ampoules of 2% lidocaine HCl injection and was qualitatively analyzed using UV-Vis spectrophotometry. The study lasted for 14 days by first storing the injections in storage conditions at room temperature (25-27℃), cold temperatures (5-10℃), and exposed to Ultraviolet light (380 nm). Based on the results of laboratory tests, the most suitable storage condition used for storing lidocaine HCl injection was cold storage (5-10℃) because there was no shift in the maximum wavelength as occurred during the 14th day of UV exposure storage.